Beginning HTML and CSS - Larsen, Rob (Programmer to programmer., 2013)
Chapter 11: Working with jQuery; Why jQuery?; Adding jQuery to Your Page; jQuery Basics; jQuery and the DOM; Managing Events with jQuery; Summary; Chapter 12: jQuery: Beyond the Basics; Ajax with jQuery; jQuery UI; Summary; Chapter 13: Checklists; Search Engine Optimization Checklist; Accessibility Checklist; Appendix A: Answers to Exercises; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chapter 6; Chapter 7; Chapter 8; Chapter 9; Chapter 10; Chapter 11; Chapter 12; Chapter 13; Appendix B: HTML Element Reference; Appendix C: CSS Properties; Font Properties; Text Properties.